An Asymptotic Formula for r-Bell Numbers with Real Arguments. (13th February 2013) - Corcino, Cristina B.; Corcino, Roberto B.
Abstract : The r -Bell numbers are generalized using the concept of the Hankel contour. Some properties parallel to those of the ordinary Bell numbers are established. Moreover, an asymptotic approximation for r -Bell numbers with real arguments is obtained.